The hyperosmolar solution for infusion sorbilact application in clinic of urgent neurosurgery - Polischuk, N. E.; Kamynsky, A. A.; Litvinenko, A. L.; Demchuk, S. A.; Smolanka, V. I. (Ukrainian Neurosurgical Journal)
The results of undertaken investigations evidence that application of hyperosmolar preparation sorbilact allowed to an achieve high efficacy in treatment of brain edema of different etiology and is recommended for use in neurological and neurosurgical practice.